Dana syirkah temporer dan corporate governance Mechanism terhadap kinerja maqasid syariah bank syariah - Priatna, Andika (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2018)
This study aims to determine the effect of temporary syirkah funds, board size, a board ofcommissioner meetings, board size, a board of directors meetings, the size of the shariasupervisory board, sharia supervisory board meetings, and the performance of sharia Islamicbanking in Indonesian banking. The research method used in this study is the explanatory method,the independent variables used in this study consist of temporary syirkah funds, board size, aboard of commissioner meetings, board size, a board of directors meetings, the size of the shariasupervisory board, and sharia supervisory board meetings. While the dependent variable ismaqasid sharia performance, the population in this study is the Islamic Commercial Bank (BUS),the samples were taken are 6 Islamic banks. Simultaneous temporary syirkah funds, board size,a board of commissioner meetings, board size, a board of directors meeting, sharia supervisoryboard size, and sharia supervisory board meetings have a positive and significant effect onmaqasid sharia performance.